If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying (-1x + 9) * 4 = 0 Reorder the terms: (9 + -1x) * 4 = 0 Reorder the terms for easier multiplication: 4(9 + -1x) = 0 (9 * 4 + -1x * 4) = 0 (36 + -4x) = 0 Solving 36 + -4x = 0 Solving for variable 'x'. Move all terms containing x to the left, all other terms to the right. Add '-36' to each side of the equation. 36 + -36 + -4x = 0 + -36 Combine like terms: 36 + -36 = 0 0 + -4x = 0 + -36 -4x = 0 + -36 Combine like terms: 0 + -36 = -36 -4x = -36 Divide each side by '-4'. x = 9 Simplifying x = 9
| 7a-20=80 | | 3(2y+5)=30 | | 23x-5=25x-5 | | 2x+5=133 | | Y=58x+228 | | 7=5k-3 | | 5x-1=-5x+1 | | 7/2*63=7/2*2/7 | | M-5=11 | | (-x+7)*3= | | (g-7)(g+9)= | | 4v=8e-g | | 10m+3=38 | | 0.9=-log | | 2*-1=0 | | -2x^2-22x+24= | | 4v=8e | | 2x+2=0.50x+11 | | 5a+12=36 | | 3n-5n=3 | | (7x-6)=90 | | 5/7x35 | | 5(2x+6)=-3(4x-1) | | 4(m-2)=14 | | (4x+3)+(-2x+4)=y | | 4.7p+8.7p+2.6p=93.96 | | 18x-36=12x-24 | | 2.2=-log(x) | | -15x+43=-10x+28 | | 47=2+9w | | 3(5y+5)=5y+45 | | 4a+8b=x |